A Commentary on “Effective Dose of Epidural Hydromorphone for Analgesia Following Caesarean Section in Using Modified Dixon Sequential Method” [Response to Letter] - Liu QQ; Mao M; Lin NH; Xu CY; Li Q; Jiang CS; Feng SW; Yuan HM (Journal of Pain Research)
Qiao-Qiao Liu,1,* Mao Mao,1,* Ning-Hua Lin,2,* Chen-Yang Xu,1,* Qian Li,1 Chang-Shuo Jiang,1 Shan-Wu Feng,1 Hong-Mei Yuan1 1Department of Anesthesiology, Women’s Hospital of Nanjing Medical University, Nanjing Women and Children’s Healthcare Hospital, Nanjing, 210004, People’s Republic of China; 2Department of Anesthesiology, Nanjing Drum Tower Hospital, The Affiliated Hospital of Nanjing University Medical School, Nanjing, 210008, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shan-Wu Feng; Hong-Mei Yuan, Department of Anesthesiology, Women’s Hospital of Nanjing Medical University, Nanjing Women and Children’s Healthcare Hospital, No. 123, Tianfei Lane, Mochou Road, Nanjing, Jiangsu, People’s Republic of China, Email Shanwufeng666@163.com; yuanhm667@126.com